Effect of hydroxypropyl-β-cyclodextrin on the ocular bioavailability of dexamethasone from a pH-induced mucoadhesive hydrogel - Kesavan K.; Kant S.; Singh P.N.; Pandit J.K. (My University, 2025)
Purpose: Dexamethasone (DXN) is an effective anti-inflammatory drug in the treatment of acute and chronic eye disease such as uveitis. It is relatively lipophilic and permeates biological membranes quite easily. However, its low aqueous solubility limits its clinical usefulness. To circumvent this problem Hydroxypropyl-β-cyclodextrin (HP-β-CD) was used as solubilizer and penetration enhancer for DXN. The purpose of this study was to develop HP-β-CD based pH-induced mucoadhesive hydrogel for ophthalmic delivery of DXN to treat uveitis. Materials and methods: The formation of inclusion complex of DXN with HP-β-CD was characterized in solution and solid states by phase solubility, X-ray diffractometry and IR spectrum analyses. To improve ocular retention and sustained action Carbopol 980 NF and sodium carboxymethylcellulose (NaCMC) were added to the formulations as phase transition and mucoadhesive agents, respectively. Results: The HP-β-CD-based hydrogel system enhanced the solubility of DXN and the apparent stability constant (k′) of the DXN-HP-β-CD inclusion complex was found to be 258.62M -1. The optimum concentrations of Carbopol 980NF and NaCMC for the mucoadhesive hydrogel were 0.2% (w/v) and 0.4% (w/v), respectively. This mucoadhesive hydrogel could flow freely under non-physiological condition and showed the character of pseudoplastic fluid under both physiological and non-physiological conditions. In vitro release of DXN from the HP-β-CD complex in simulated tear fluid (STF, pH- 7.4), was influenced significantly by the properties and concentration of Carbopol and NaCMC. In vivo studies in rabbit eye showed a marked improvement in anti-inflammatory activity of mucoadhesive hydrogel-treated eye compared with a marketed solution formulation in a uveitis-induced rabbit eye model. Conclusion: The developed HP-β-CD-based mucoadhesive system is a viable alternative to conventional eye drops of DXN due to its ability to enhance bioavailability through its longer precorneal residence time and ability to sustain the release of the drug. © 2011 Informa Healthcare USA, Inc.